Evaluating the Effect of Chloroform and Water Extract of Satureja khuzistanica on the Expression of Bcl-2 and Bax in Gastric Cancer Cell Line - Bagher Biglak; Asghar Tanomand; Leyla Açik; Farzad Arjomandi Rad; Gholamreza Shahsavari; Saman Kazemi; Hossein Soltanzadeh (Gazi Medical Journal)
Objective: Gastric cancer is a complex disease. Natural antioxidant sources without toxic side effects are suitable for the treatment and management of diseases such as cancer. Satureja khuzistanica (S. khuzistanica) is an endemic plant in southern Iran. Despite numerous articles published about this plant, a limited number of studies have been conducted on its anticancer effects. Therefore, this study was conducted to evaluate the cytotoxic and apoptotic effects of this plant on the gastric cancer cell line. Methods: The antimicrobial activities of chloroform and water extracts were screened against pathogenic bacteria [Helicobacter pylori (H. pylori)]. The cytotoxicity effect of the extracts was evaluated using an microculture tetrazolium assay on gastric cancer cell lines (AGS and KATO III) and normal gingival fibroblasts. The expression of Bax and Bcl-2 was evaluated using real-time polymerase chain reaction. Finally, all data were analyzed using REST software. Results: Both extracts showed good inhibitory activity against H. pylori. In addition, extracts showed cytotoxic activity against gastric cancer cell lines. Treatment of S. khuzistanica cells increased and decreased the expression of Bax and Bcl-2 apoptotic genes, respectively (p<0.05). In addition, in HGF cells, there were no cytotoxic effects or apoptosis induction triggered by the extracts. Conclusion: The chloroform extract had more cytotoxic and apoptotic effects than the water extract. The extracts could have anticancer and apoptotic effects on the gastric cancer cell line.